Regulating the Surface Passivation and Residual Strain in Pure Tin Perovskite Films - Hu, Manman; Nie, Riming; Kim, Hyeonwoo; Wu, Jianchang; Chen, Shanshan; Park, Byung-Wook; Kim, Gwisu; Kwon, Hyoung-Woo; Seok, Sang Il (ACS Energy Letters, 2021)
The passivation of electronic defects at the surfaces and grain boundaries of perovskite materials is one of the most important strategies for suppressing charge recombination in perovskite solar cells (PSCs). Although several passivation molecules have been investigated, few studies have focused on their application in regulating both the surface passivation and residual strain of perovskite films. In this study, the residual strain distribution profiles of the Cs0.1FA0.9SnI3 perovskite thin films and their effect on the photovoltaic device efficiencies were investigated. We found a gradient distribution of the out-of-plane compressive strain that correlated with the compositional inhomogeneity perpendicular to the substrate surface. By deliberately engineering dual effects of the surface passivation and residual strain, we achieved a record power conversion efficiency of up to 9.06%, the highest ever reported in a typical n-i-p architecture.
CRIS-Team Scopus Importer:2021-11-05